PENGARUH MEDIA VIDEO ANIMASI LALU LINTAS TERHADAP PERILAKU DISIPLIN BERLALU LINTAS ANAK USIA 5-6 TAHUN - Lestari, Wici; Suningsih, Taruni (Bunayya, 2025)
Disciplined behavior reflects an attitude of obedience, orderliness, and regularity that is formed through the learning process and the influence of the individual's environment. Basically, behavior is a human action that can be observed through interaction with the environment. This study aims to determine the effect of animated traffic video media on traffic discipline behavior in children aged 5-6 years. This research method uses a pre-experimental with a one-shot case study design. The research sample consisted of 15 children aged 5-6 years. Data were collected through observation using checklist sheets, oral tests, and documentation. The results of the t-test statistical analysis showed a value of 5.35 compared to the t-table value of 1.761, which means that there is a significant effect of the use of animated traffic video media on children's traffic discipline behavior at Az-Zahrah Islamic Kindergarten, Palembang. After the application, the children were able to watch the video until the end, not make a fuss, wait their turn when asked by the teacher, know the regularity of traffic, cross at the zebra crossing, and look right and left before crossing the road.